202: THE RELATION BETWEEN IRANIAN MEDICAL SCIENCE RESEARCH IN WEB OF SCIENCE DATABASE AND BURDEN OF DISEASE IN IRAN. (8th February 2017) - Foroughi, Zahra; Davodi, Ali; Alizadeh-Navaei, Reza
Abstract : Background and aims: Scientific productions have been accelerated in Iran in past decades but their association with health problems and disease burden is doubtful. The aim of this study was to assess the relationship between Iranian scientific productions (published in 2010–2015) with disease burden in Iran using Web of Science database. Methods: Data was collected using Scientometric indicators, direct observation, and note taking. The current research included all articles written by Iranian researchers during 2010 to 2015which were published in Web of Science – indexed journals. The search was limited to the affiliation 'Iran' and was performed using different keywords including road accident, ischemic heart diseases, major depression disorders, and cerebral vascular diseases, Back Pain, Osteoarthritis, Knee, Anemia, Iron-Deficiency, Bipolar Disorder and Pulmonary Disease, Chronic Obstructive. These were believed to have the highest disease burden. Then, the scientometric outputs were recorded and the relationship between scientific productions with disease burden was investigated. Results: In total, 1800 articles had been published in Web of Science – indexed journals. Among them depression disorders and Cerebrovascular Disorders had the highest (1296 records) and lowest (18 records) records, respectively. Major depression disorders were found to have the greatest h-index and the highest percentage of scientific productions with at Average Citations per Year was associated with Major depression. There was a direct correlation between years of life lost due to premature mortality (r=0.8, P=0.2), years lived with disability (r=0.333, p=0.381), with scientific productions. Conclusion: our results showed Iranian scientific productions in Web of Science data set are not related to disease burden.